2015
DOI: 10.1016/j.redox.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The correlations of glycated hemoglobin and carbohydrate metabolism parameters with heart rate variability in apparently healthy sedentary young male subjects

Abstract: IntroductionSedentary lifestyle is a major risk factor for diabetes, cardiovascular and many other age-related diseases. Heart rate variability (HRV) reflects the function of regulatory systems of internal organs and may sensitively indicate early metabolic disturbances. We hypothesize that quantitative and qualitative changes of HRV in young subjects may reflect early metabolic derangements responsible for further development of clinically significant disease.AimThe aim of our study was to determine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…As we have recently hypothesized [18], the interpretation of decreased HRV may not be simply limited to an autonomic dysfunction and increased sympathetic tone. The negative correlations of HRV parameters with weight, visceral fat, BMI, and a number of carbohydrate metabolism parameters in apparently healthy sedentary subjects also confirm this hypothesis [23]. The energetic deficiency as well as chronic hypoxia and persistence of oxidative stress seem to play major roles in HRV suppression in MS patients.…”
Section: Discussionsupporting
confidence: 62%
“…As we have recently hypothesized [18], the interpretation of decreased HRV may not be simply limited to an autonomic dysfunction and increased sympathetic tone. The negative correlations of HRV parameters with weight, visceral fat, BMI, and a number of carbohydrate metabolism parameters in apparently healthy sedentary subjects also confirm this hypothesis [23]. The energetic deficiency as well as chronic hypoxia and persistence of oxidative stress seem to play major roles in HRV suppression in MS patients.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with this is recent data generated on C. elegance model regarding integration of stress induced responses of nervous system with metabolic adaptations [34]. It was shown that the flight response mediated by tyramine (worm analog of catecholamines) in the end leads to stimulation of insulin-IGF-1 signaling and have the opposite effect to longevity-promoting stress responses to heat, starvation, glucose restriction or exercise [35][36][37]. If hypothetically translated to modern humans it can provide accurate mechanistical explanations why emotional stress accompanied with sedentary behaviors may have detrimental health consequences associated with both excessive insulin and adrenaline signaling causing atherosclerosis [23], contributing among the other factors to insulin resistance and accelerated aging [38] but can be reversed by exercise or fasting [39].…”
Section: The Evidence Of Pandemic Glucose Toxicity In Human Populatiosupporting
confidence: 61%
“…It was demonstrated that Amaranth oil supplementation provided significant improvement of gastric mucosa morphological pattern and also had a positive effect on heart rate variability [5]. In a separate study we demonstrated that H. pylori in apparently healthy sedentary young male subjects is associated with higher heart rate, sympathetic activity and insulin resistance, however, we detected no changes in parameters reflecting inflammatory profile, metabolic parameters or oxidative stress [6][7][8]. In summary, there is a growing evidence of systemic metabolic effects of H. pylori infection not only in patients with overt gastrointestinal disorders, but also in apparently asymptomatic healthy subjects.…”
mentioning
confidence: 56%